2009
DOI: 10.1017/s1368980009991996
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a web-based dietary questionnaire designed for the DASH (Dietary Approaches to Stop Hypertension) diet: the DASH Online Questionnaire

Abstract: Objective-With the upsurge in online dietary modification programmes, online dietary assessment tools are needed to capture food intake. Although the DASH (Dietary Approaches to Stop Hypertension) diet is recommended by the US Department of Agriculture, there are no online instruments that capture DASH food servings. Our objective was to assess the validity of a new, short, online dietary questionnaire developed to capture intake of DASH food servings. The DASH Online Questionnaire (OLQ) was validated against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 25 publications
6
30
0
Order By: Relevance
“…Significant overestimations were observed only for a few nutrients (for example, EPA), which could be partly explained by the different nutritional contribution of the foods grouped together in the web-FFQ database (for example, types of fish) compared with specific food items in the FRs. Another factor to consider is the duration of the reference measure: 3 days of record may not have been enough to capture the real dietary intakes of the participants over 1 month, particularly for foods that are not consumed frequently (Apovian et al, 2010). Correlation coefficients considered as acceptable in FFQ validation studies range from 0.4-0.7 (Willet, 1994;Willet, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant overestimations were observed only for a few nutrients (for example, EPA), which could be partly explained by the different nutritional contribution of the foods grouped together in the web-FFQ database (for example, types of fish) compared with specific food items in the FRs. Another factor to consider is the duration of the reference measure: 3 days of record may not have been enough to capture the real dietary intakes of the participants over 1 month, particularly for foods that are not consumed frequently (Apovian et al, 2010). Correlation coefficients considered as acceptable in FFQ validation studies range from 0.4-0.7 (Willet, 1994;Willet, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, differences in the frequency of consumption may be more likely to occur between a 3-day FR and a web-FFQ covering the previous month than between two FFQs covering the same period. In this regard, Apovian et al (2010) suggested that correlations may improve with tracking of more days of FR. Moreover, an important observation is that the IA-FFQ, like the web-FFQ, included questions about added fat and fat used for cooking and correlations for fat variables were much stronger between the IA-FFQ and the web-FFQ than between the 3-day FR and the web-FFQ.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the research works that use Web-based food frequency questionnaires has increased in the last few years [6,23,24,26,29,30] and the validity and reproducibility of Web-based FFQs has also been evaluated [22,25,27,28].…”
Section: Web-based Food Frequency Questionnaires (Web-ffqs)mentioning
confidence: 99%
“…FFQs [22,6,23,24,25,26,27,28,29,30], online 24 hour dietary recalls [8,31,32,33,34] and combinations of both FFQs and 24HDRs [35,36,37,38]. A few similar reviews or states-of-the-art are found in the literature [39,40,1,41].…”
Section: Introductionmentioning
confidence: 99%
“…They therefore offer a new dietary assessment tool to measure adherence to the DASH diet, shown previously to reduce blood pressure and reduce risk of heart disease and stroke (13) . Their article provides some useful perspective on dietary measures to prevent high blood pressure.…”
Section: Assessment Of Diet For Prevention Of High Blood Pressurementioning
confidence: 99%